A mononuclear dysprosium(iii) single-molecule magnet with a non-planar metallacrown. (21st May 2019) - Jiang, Xiao-Feng; Chen, Ming-Guang; Tong, Jia-Ping; Shao, Feng
Abstract : This work demonstrates an unusual mononuclear Dy III single-molecule magnet with a non-planar metallacrown which formed by diamagnetic Ga III ions. Abstract : A mononuclear dysprosium(iii )/gallium(iii ) metallacrown complex, [DyGa4 (Hnha)2 (nha)4 (NO3 )(C5 H5 N)4 ](C5 H6 N)2 ·(H2 O)10 (1 ·H2 O), was synthesized with a hydroxamic ligand: 3-hydroxy-2-napthanoic hydroxamic acid (H3 nha). Meanwhile, the molecular structure was confirmed by single-crystal X-ray diffraction analysis, and the Dy III centre is nine-coordinate and adopts a distorted tricapped trigonal prism coordination geometry as indicated by continued shape measurements (CShM) SHAPE analysis. In addition, the dynamic magnetization studies revealed that complex1 displayed field-induced single-molecule magnet behaviour with an effective energy barrier U eff = 26.4 K and pre-exponential factor τ 0 = 2.2 × 10 −6 s.